Advances in filler-crosslinked membranes for hydrogen fuel cells in sustainable energy generation - Aminul Islam; Mamun Shahriar; Md. Tarekul Islam; Teo, Siow Hwa; M. Azizur R. Khan; Yap, Taufiq Yun Hin; Suman C. Mohanta; Ariyan Islam Rehan; Adiba Islam Rasee; Khadiza Tul Kubra; Md. Munjur Hasan; Md. Shad Salman; et al. (Elsevier Ltd., 2025)
Fuel cell membranes can be used in various ways to achieve zero-emission transport and energy systems, which offer a promising way to power production due to their higher efficiency compared to the internal combustion engine and the eco-environment. Perfluoro sulfonic acid membranes used for proton exchange membranes (PEMs) have certain drawbacks, like higher fuel permeability and expense, lower mechanical and chemical durability, and proton conductivity under low humidity and above 80 °C temperature. Researchers have drawn their attention to the production of polymer electrolyte membranes with higher proton conductivity, thermal and chemical resilience, maximum power density, lower fuel permeability, and lower expense. For sustainable clean energy generation, a review covering the most useful features of advanced material-associated membranes would be of great benefit to all interested communities. This paper endeavors to explore several types of novel inorganic fillers and crosslinking agents, which have been incorporated into membrane matrices to design the desired properties for an advanced fuel cell system. Membrane parameters such as proton conductivity, the ability of H2 transport, and the stability of the membrane are described. Research directions for developing fuel cell membranes are addressed based on several challenges suggested. The technological advancement of nanostructured materials for fuel cell applications is believed to significantly promote the future clean energy generation technology in practice.